Arterial stiffness and hypertension - Kim, Hack-Lyoung (Clinical hypertension, 2023)
Arterial stiffness and hypertension are closely related in pathophysiology. Chronic high blood pressure (BP) can lead to arterial wall damage by mechanical stress, endothelial dysfunction, increased inflammation, oxidative stress, and renin–angiotensin–aldosterone system (RAAS) activation. Hypertension also increases collagen fiber production and accelerates elastin fiber degradation. Stiffened arteries struggle with BP changes, raising systolic BP and pulse pressure. The resulting increased systolic pressure further hardens arteries, creating a harmful cycle of inflammation and calcification. Arterial stiffness data can predict target organ damage and future cardiovascular events in hypertensive patients. Thus, early detection of arterial stiffness aids in initiating preventive measures and treatment plans to protect against progression of vascular damage. While various methods exist for measuring arterial stiffness, pulse wave velocity is a non-invasive, simple measurement method that maximizes effectiveness. Healthy lifestyle changes, RAAS blockers, and statins are known to reduce arterial stiffness. Further research is needed to ascertain if improving arterial stiffness will enhance prognosis in hypertensive patients.